Recanalization in Uncut Roux-en-Y Reconstruction: An Animal Experiment and a Clinical Study - Wu, Feng; Ni, Zhizhan; Diao, Hongliang; Huang, Chenshen; Wang, Song; Ge, Bujun; Huang, Qi (Frontiers in Surgery, 2021)
Background: Because of the challenge of jejunal closure recanalization, uncut Roux-en-Y reconstruction remains controversial. This study aimed to investigate the incidence of recanalization after uncut Roux-en-Y reconstruction in pigs and a small number of patients. Methods: Twenty miniature pigs were subjected to distal gastrectomy and uncut Roux-en-Y reconstruction using various rows of linear staplers to block the intestine. The pigs were sacrificed, and the incidence of recanalization was investigated 1 month after the operation. From December 2018 to June 2019, 10 patients with gastric cancer who had undergone elective laparoscopy-assisted distal gastrectomy and uncut Roux-en-Y reconstruction were included in this study. The primary study outcome was recanalization of the afferent limb, demonstrated by gastrointestinal radiography 1, 3, and 6 months after surgery. Various numbers of staple lines across the afferent jejunal limb were applied for closure: 2 staple lines in 2 pigs, 4 staple lines in 6 pigs, 6 staple lines in 8 pigs, and 8 staple lines in 4 pigs. Results: Complete recanalization was detected in all 20 pigs 1 month postoperatively. Recanalization was detected in five cases (50%) by gastrointestinal radiography. Among them, 1 case of recanalization was found in the 1st month after the operation, 2 cases were found in the 3rd month, and another 2 cases were found in the 6th month. Bile reflux was detected by endoscopy in 2 patients with recanalization. Conclusions: The occurrence of afferent limb recanalization after uncut Roux-en-Y reconstruction is high, and using additional staplers alone cannot decrease the incidence of recanalization. Based on our study, uncut Roux-en-Y reconstruction is not recommended.